Perception of inequalities in the province of Córdoba: Characteristics and theoretical implications - Nazareno, Marcelo Gabriel; Santillán Pizarro, María Marta (Universidad Nacional de Villa María, 2018)
On the base of a stochastic survey in the Province of Córdoba, we address two issues regarding inequality perceptions. First, inequality level´s perception in different dimensions (in general terms, job access, health, education, housing and political influence) taking into account different territorial reference (city of residence, province and country). Second, if the theoretical expectation of different theories finds support in the evidence provide by the relationship between inequality perceptions and relevant variables. Regarding the first point, our findings are that, in the context of perception of high inequality´s level, there are noticeable difference among different dimensions, being health and educations which ones show the lower levels and, regarding the second point, that the evidence is consistent about the power resource theory, is contradictory with the median vote theory´s expectations y do not offer solid support for the social distance theory.